Peningkatan Pengetahuan Orangtua melalui Kegiatan Parenting dalam Upaya Mendukung Kegiatan PAUD Holistik Integratif di Kelompok Bermain Nirwana 1 Semanding Tuban - Samu (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
The purpose of parenting class activities is to increase parental knowledge in supporting holistic integrative early childhood education programs. The activities carried out use an educative approach, with the method of discussion, and question and answer lectures. The material provided includes parental responsibilities in child care, understanding between educators and parents, types of Holistic Integrative Early Childhold Education services and types of parenting activities. The executors of the activities were 1 overseer from the Tuban Education Office, teachers and operators in the Nirwana 1 playgroup, and the target activities were 22 parents of students. The results of the activities that have been carried out have resulted in an increase in knowledge scores with an average pre-test score of 61 and a post-test score of 76. The results of this activity are expected to have an impact on increasing parental participation in integrative holistic PAUD activity programs